Word 2019 for dummies - Gookin, Dan (--For dummies., 2019)
The bestselling beginner & rsquo;s guide to Microsoft Word Whether you've used older versions of this popular program or have never processed a single word, this hands-on guide gets you going with the latest version of Microsoft Word. In no time, you'll begin editing, formatting, proofing, and dressing up your Word documents like a pro. In this leading book about the world & rsquo;s number one word processing application, Dan Gookin talks about using Microsoft Word in friendly, easy-to-follow terms. Focusing on the needs of the beginning Word user, it provides everything you need to know about Word & mdash;without any painful jargon. Covers the new and improved features found in the latest version of Word Create your own templates Explains why you can & rsquo;t always trust the spell checker Offers little-known keyboard shortcuts If you & rsquo;re new to Word and want to spend more time on your actual work rather than figuring out how to make it work for you, this new edition of Word X For Dummies has you covered.